Fotografer Jalanan Kajian Atas UUD ITE dan Hukum Ekonomi Syari’ah Studi di Kawasan Makam Gusdur Jombang - Muhamad Ali Tamrin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
Photography is an inseparable part of human life in this millennial era, especially for those who like to travel, the tendency to capture every moment has almost become a tradition, but if done by others without permission, problems arise, how the legal impact on the practice of street photographers in terms of the ITE Law and Sharia Economic Law. The data collection method uses documentation, interviews, and observation methods. After that, it is studied with a descriptive analytical approach, which examines data collected in the field about street photographers, and the information is then studied through the lens of shari'ah economic law thinking. The results of the study concluded that the practice of photography on Gus Dur's tomb. Islamic law considers shooting without permission an incomplete contract, because in reality the photographer does not meet any of the conditions of permission and approval and there is no willingness. It will remain that if there is a forced purchase, then the practice is not legal. Another thing that the photographer did was a valid contract according to 'urf because of the khiyar conditions and khiyar majlis. Furthermore, photographers can be charged with the ITE Law if pilgrims are not willing and feel aggrieved. In the end, the author suggests that for the perfection of the contract, photographers should have permission first if they want to photograph someone. This is for mutual comfort and benefit, more than that ethics in business can be carried out on all fronts, including photographer services.